ADMINISTRASI PERSONALIA GURU - Meti Fatimah; Hafidz Abdul Rozaq; Muhammad Fathin Abdul Ghoffar (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Personnel administration is a crucial aspect of educational management, particularly in efforts to improve the effectiveness and efficiency of the performance of educators (teachers) and educational staff (staff). Teachers and school staff are key assets in carrying out the teaching and learning process and administrative services within the school environment. Therefore, personnel administration management, which includes workforce needs planning, recruitment, placement, training, performance appraisal, promotion, and dismissal, is carried out systematically and continuously. Therefore, it is crucial to continuously improve the quality of teacher and staff personnel administration through appropriate policies. The main goal is to ensure that every employee, both educational and non-educational, can work according to their abilities and responsibilities to achieve educational goals.